To solve the system of equations using elimination, we need to eliminate one variable by adding or subtracting the two equations. In this case, we can eliminate the x variable.
First, let's multiply the first equation by 2 to make the coefficients of x the same:
-8x - 6y = 6
Now, we can add the two equations together to eliminate x:
(-8x - 6y) + (4x + 6y) = 6 + (-6)
-8x + 4x - 6y + 6y = 0
-4x = 0
x = 0
Now that we have x = 0, we can substitute it back into either of the original equations. Let's use the first equation:
-4(0) - 3y = 3
0 - 3y = 3
-3y = 3
y = -1
Therefore, the solution to the system of equations is x = 0 and y = -1
mark me as brilliant